Molecular surveillance of Salmonella Typhimurium and its respiratory tract pathology in pet birds from Kerala - C. Udhayakumar; I.S. Sajitha; K.S. Prasanna; K. Krithiga; S.S. Devi; R. Bharathi; Nisna Niyas; P. M. Priya; Asha Rajagopal (Journal of Veterinary and Animal Sciences, 2025)
A total of 76 pet bird carcasses were studied for gross lesions and later histopathology. Molecular investigation detected Salmonella typhimurium in 28.6 per cent of psittacine and passerine birds. Twelve out of forty-two and two out of seven psittacine and passerine birds, respectively, were found to be infected with S. typhimurium. Regarding columbid and ornamental birds, 22.2 per cent of birds showed positive results. The upper respiratory tract revealed necrotic changes on both the respiratory epithelium and the secretory glands, together with loss of epithelial cilia. Histopathological analysis of respiratory organs of birds positive for the Salmonella organisms showed lesions in both upper and lower respiratory tract.